Re-imagining crisis care: experiences of delivering and receiving the Assured brief psychological intervention for people presenting to Emergency Departments with self-harm - Shah, Neha; O’Keeffe, Sally; Hayward, Sam; Suzuki, Mimi; McCabe, Rose (Frontiers in Psychiatry, 2024)
Background: Risk of suicide is increased immediately following emergency department (ED) attendance for self-harm and/or suicidal ideation. Evidence suggests that brief psychological interventions delivered in EDs are effective for self-harm. The Assured intervention comprises an enhanced biopsychosocial assessment in the ED, collaborative safety planning and three rapid solution focused follow-up sessions.Aim: We addressed the following research questions: What were ED mental health liaison practitioners' and patients' experiences of the Assured intervention? What were the barriers and facilitators? What might the mechanisms be for improving experiences and outcomes? Methods: We conducted a feasibility study of the Assured intervention in four EDs in Southeast England. Semi-structured interviews were conducted with 13 practitioners and 27 patients. Interviews were transcribed, coded line-by-line in Nvivo and thematically analysed using an inductive approach. Inter-rater reliability was calculated with a kappa coefficient of 0.744.Five overarching themes were identified:1. The intervention mostly gives agency and hope to highly distressed patients, and helps patients implement strategies to support their mental health; however potential adverse effects were patients becoming overwhelmed or triggered. 2. The intervention works by creating a space for patients to express what is important to them; facilitating insight and reflection, validating emotions, and building self-esteem, helping patients manage boundaries and trial what works to support their mental health. 3. The intervention re-imagines the practitioner-patient relationship and facilitates trust and new possibilities for patients who have difficult relationship and help-seeking histories. 4. The intervention requires a significant shift in professional culture and a new way of working practically by doing follow-up work, moving from a reactive to a more proactive role. This needs support and supervision but is rewarding for practitioners. 5. The intervention challenges the limitations of point-of-crisis care by opening up a new and timely therapeutic space and holding and supporting patients to access further support.Providing rapid therapeutic follow-up support after attending ED with self-harm/suicidality can begin to address existing failures in the mental health system, where patients feel unsupported and -at times -judged by professionals, by supporting people and fostering agency. However, there are significant cultural and service pathway barriers.